2017
DOI: 10.1002/aqc.2835
|View full text |Cite
|
Sign up to set email alerts
|

The value of small, natural and man‐made wetlands for bird diversity in the east Colombian Piedmont

Abstract: 1. Small wetlands are considered a refuge for biodiversity, but the importance of natural and man-made lentic wetlands for the maintenance of bird diversity in human-dominated landscapes is not well-known in the Neotropics.2. This study evaluated the influence of the types and origins (natural or man-made) of lentic wetlands on bird diversity of three guilds (aquatic, semi-aquatic and landbirds) in the Meta Piedmont, Colombia.3. The species richness and the structure and composition of each bird guild were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…In this scenario, artificial wetlands can play an important role in maintaining biodiversity (Cardoso and Loures-Ribeiro 2017). Reservoirs are noteworthy among these environments as they provide habitats for several wetland-dependent species, particularly waterbirds (Sebastián-González et al 2010;Murillo-Pacheco et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, artificial wetlands can play an important role in maintaining biodiversity (Cardoso and Loures-Ribeiro 2017). Reservoirs are noteworthy among these environments as they provide habitats for several wetland-dependent species, particularly waterbirds (Sebastián-González et al 2010;Murillo-Pacheco et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of wetland loss ranges from minor losses in boreal region countries to >90% losses in parts of Europe [4] and New Zealand [5]. This reduction in wetlands, which animals rely on for foraging, breeding, and nesting habitat [6,7], combined with increasing nutrient inputs from agricultural land use, has resulted in major eutrophication and biodiversity loss [8]. Conversely, restoring natural wetlands and establishing constructed treatment wetlands can provide environmental benefits, including buffering runoff, reducing erosion, attenuating nutrients and other contaminants, and mitigating biodiversity loss [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have found that human-influenced wetlands could provide alternative, complementary habitats for some species ( Fidorra et al, 2016 ; Giosa, Mammides & Zotos, 2018 ; Kloskowski et al, 2009 ; Li et al, 2013 ; Márquez-Ferrando et al, 2014 ). In some cases, the transformation from natural to human-influenced wetlands has increased bird diversity due to enhanced habitat heterogeneity ( Murillo-Pacheco et al, 2018 ). Also, aquaculture commercial fishponds can provide essential feeding grounds for waterbirds ( Navedo et al, 2015 ; Ramirez et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%